Virtual Reality For Anxiety Management: Exposure Mechanisms, Immersion, And Relaxation Effects In A Narrative Review - Choiriah Rika; Salsabila Rizqa Annisa; Ny. Rizka Miftahul Jannah; Konto Iskandar Dinata (CV. Doki Course and Training, 2025)
Anxiety disorders are highly prevalent conditions that significantly affect individuals’ emotional and physiological functioning. This study aims to narratively examine the effectiveness of various Virtual Reality (VR)-based interventions in reducing anxiety across different populations. A narrative literature review was conducted using Google Scholar and ScienceDirect in November 2025. The inclusion criteria consisted of empirical articles published between 2015 and 2024, employing VR interventions to reduce anxiety, and available in Indonesian or English. Of the 46 articles initially identified, 8 met the eligibility criteria and were analyzed. The results indicate that VR interventions including VR relaxation, Virtual Reality Exposure Therapy (VRET), VR-murottal, and VR-CBT produce significant reductions in anxiety, such as decreased pre-operative anxiety (p = 0.000) and increased self-confidence in individuals with social phobia. However, the effectiveness of VR varies across populations and modalities, and several limitations were noted, including heterogeneity in study designs and incomplete reporting of quantitative outcomes. Overall, VR demonstrates substantial potential as both a primary and adjunctive intervention for anxiety management, although further research with more standardized procedures is needed.